Legal Security Differences: Co-operative Comparison Between The United Kingdom And The Netherlands - Colon, Damy W. (Archives of Business Research, 2017)
This paper explores the co-operative compliance approaches implemented by the UK and the Netherlands. The commonly applied legal co-operative compliance framework is used to compare both countries. Both the UK and Dutch approach on co-operative compliance are analyzed with the framework. It is concluded that the UK co-operative compliance approach creates legal security. The Dutch co-operative compliance approach is not creating legal security. These findings are elaborated considering common and civil law. Moreover, the differences in co-operative compliance are discussed in an international context. It is concluded, that from an international perspective the UK co-operative compliance approach is desirable as long as other countries follow the Dutch co-operative compliance approach.